2021
DOI: 10.5498/wjp.v11.i11.1065
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in schizophrenia could be interleukin-33-mediated

Abstract: Recent epidemiological and genetic studies have revealed an interconnection between schizophrenia and breast cancer. The mutual underlying pathophysiological mechanisms may be immunologically driven. A new cluster of molecules called alarmins may be involved in sterile brain inflammation, and we have already reported the potential impact of interleukin-33 (IL-33) on positive symptoms onset and the role of its soluble trans-membranes full length receptor (sST2) on amelioration of negative symptoms in schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…[1] Recent studies have suggested a possible association between cancer and schizophrenia, although the nature of this relationship is not yet fully understood. [1,2] Research on schizophrenia through genome-wide association studies (GWASs) has uncovered genetic similarities and some immune-related features that overlap with breast carcinoma. [1] Possible factors contributing to this association are shared genetic risk factors and similar lifestyles between the 2 conditions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1] Recent studies have suggested a possible association between cancer and schizophrenia, although the nature of this relationship is not yet fully understood. [1,2] Research on schizophrenia through genome-wide association studies (GWASs) has uncovered genetic similarities and some immune-related features that overlap with breast carcinoma. [1] Possible factors contributing to this association are shared genetic risk factors and similar lifestyles between the 2 conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Possible factors contributing to this association are shared genetic risk factors and similar lifestyles between the 2 conditions. [1,3] In addition, certain medications used to treat schizophrenia, such as antipsychotics, have been associated with an increased risk of breast cancer and colorectal cancer. [3][4][5] However, the evidence for this association is limited and conflicting, [3] and further research is needed to better understand the link between these 2 conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations